The Level of Knowledge, Mother's Employment Status, and Family Support on Toddler Visits to Posyandu in Banjar Regency - Muhammad Syarwani; Yanti, Rusmini; Anwar, Rosihan; Aprianti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2025)
Posyandu plays a crucial role in bringing promotive and preventive efforts closer to the community, especially in improving nutritional status and maternal and child health. However, low community participation in visiting Posyandu remains an issue in the working area of the Sambung Makmur Community Health Center. This study aims to analyze the factors influencing toddler visits to Posyandu in this area. This research employs a cross-sectional approach. The sampling technique used is purposive sampling, with a total of 76 respondents from 305—mothers with toddlers aged 12–59 months registered at five Posyandu in the working area of the Sambung Makmur Community Health Center. Data were collected through interviews using a questionnaire that measured variables such as the mother's knowledge level, employment status, family support, and toddler visits to Posyandu. Bivariate analysis showed that the mother's knowledge level (p-value = 0.000, correlation coefficient 0.529), the mother's employment status (p-value = 0.000, correlation coefficient 0.547), and family support (p-value = 0.000, correlation coefficient 0.549) all had significant relationships with the frequency of toddler visits to Posyandu. These findings indicate the importance of improving maternal knowledge, considering maternal employment status, and strengthening family support to increase toddler visits to Posyandu.